Avian megabacteriosis: brief review (Research, Society and Development, 2022)
Megabacteriosis is the general designation for an important avian infectious disease that was first diagnosed in budgerigars, canaries and ostriches but in the recent years, the syndrome has been found in other species, including mammals. Despite the science efforts, the taxonomic classification of the microorganism that causes the disorder is still not well established. The existence of assymptomatic subjects suggest that the natural reservoir plays an important role on the widespread of the infection and contribute to the controversial aspects related to the agent’s role as primary pathogen. Several techniques have been experimentally tested to produce more sensibility and specificity on the diagnostic of the ill. Although the proventriculitis is not only caused by Macrorhabdus ornithogaster, it is the most common clinical expression associated with megabacteriosis. Apparently, the polyenes macrolides have been successfully used to the treatment of the ill. However, new studies must be stimulated to properly elucidation of these aspects promoting considerable consensus between clinicians and the laboratories.